Circulating biomarkers in acute myofascial pain: A case–control study. Issue 37 (September 2016) - Grosman-Rimon, Liza; Parkinson, William; Upadhye, Suneel; Clarke, Hance; Katz, Joel; Flannery, John; Peng, Philip; Kumbhare, Dinesh
Abstract : Abstract: The aims of the present study were to compare levels of circulating inflammatory biomarkers and growth factors between patients with myofascial pain syndrome (MPS) and healthy control participants, and to assess the relationship among inflammatory markers and growth factors in the two groups. Biomarkers levels were assessed in patients (n = 37) with myofascial pain complaints recruited from the hospital emergency department and non-MPS controls (n = 21), recruited via advertisements in the hospital and community. Blood levels of the cytokines, namely, interleukin-6 (IL-6), tumor necrosis factor (TNF), and interleukin-12 (IL-12), and the chemokine, namely, monocyte chemoattractant protein-1 (MCP-1), macrophage-derived chemokine (MDC), eotaxin, granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin-8 (IL-8), and macrophage inflammatory proteins-1β (MIP-1β) were significantly higher in patients with MPS than controls. The results of the growth factor analyses revealed significantly higher levels of fibroblast growth factor-2 (FGF-2), platelet-derived growth factor (PDGF), and vascular endothelial growth factor (VEGF) in MPS patients versus controls. The pattern of correlation coefficients between cytokines and growth factors differed considerably for MPS patients and controls with far fewer significant positive coefficients observed in the controls. Serum inflammatory and growth factor biomarkers were elevated in MPS patients. Inflammatory biomarkers and growth factor levels may play an important role in the onset and maintenance of MPS and therefore may be useful in the diagnosis and treatment of MPS. Understanding the mechanisms of inflammation in MPS necessitates future research.